Brivaracetam add-on treatment in pediatric patients with severe drug-resistant epilepsy: Italian real-world evidence. (November 2022) - Russo, Angelo; Pruccoli, Jacopo; Cesaroni, Carlo Alberto; Belotti, Laura Maria Beatrice; Zenesini, Corrado; Bonanni, Paolo; Boni, Antonella; Cesaroni, Elisabetta; Coppola, Giangennaro; Cordelli, Duccio Maria; Danieli, Alberto; Mancardi, Maria Margherita; et al.
Highlights: Brivaracetam (BRV) is an option for severe pediatric drug-resistant epilepsy. Epilepsy onset >12 months is associated with a better prognosis after BRV. Greater epilepsy duration and seizure frequency associate with a worse prognosis. Discontinuation of BRV may be due to lack of efficacy, in severe pediatric epilepsy. Abstract: Purpose: : To report the efficacy and tolerability of brivaracetam (BRV) in add-on therapy in pediatric patients with severe drug-resistant epilepsy. Prognostic factors of clinical outcome were also analyzed. Methods: : This Italian multicenter retrospective observational study was conducted on 45 pediatric patients with severe drug-resistant epilepsy, treated with BRV for at least 1 month and with a follow-up >6 months. Demographic, clinical, and treatment variables were assessed at T0 (baseline, BRV introduction) and T1 (6 months after BRV introduction). The response was defined as ≥50% seizure frequency reduction; responders and non-responders were then compared to assess potential prognostic factors. Results: : Forty-five patients ( M  = 28, mean age 12.4+/-4.4 years) were enrolled (focal epilepsy=14; generalized epilepsy=2; epileptic encephalopathy=29). At T1, 19/45 patients (42.2%) were responders (≥50% seizure frequency reduction), with 4 patients (8.9%) achieving a  ≥ 75% seizure reduction and 2 patients (4.4%) becoming seizure free. Epilepsy onset at >12 months of age ( p  = 0.001), disease duration ≤6 years ( p  = 0.036), and lower seizure frequency at baseline ( p  = 0.008) were the prognostic factors significantly associated with a better prognosis. No significant difference emerged for demographics, epilepsy types/etiology, intellectual disability, or therapy variables. At T1, 21 patients (46.6%) discontinued BRV, mainly due to lack of efficacy (13 subjects; 28.9%) and adverse events in 8 patients (17.8%). Conclusion: : Brivaracetam was an effective and tolerated treatment in pediatric patients with severe drug-resistant epilepsy, especially when the seizure onset was at >12 months of age, the epilepsy duration ≤6 years, and the seizure frequency before BRV treatment was low. Further and controlled studies are needed.